One perfect couple - Ware, Ruth (New York Scout Press, 2024)
"Lyla is in a bit of a rut. Her post-doctoral research has fizzled out, she's pretty sure they won't extend her contract, and things with her boyfriend, Nico, an aspiring actor, aren't going great. When the opportunity arises for Nico to join the cast of a new reality TV show, One Perfect Couple, she decides to try out with him. A whirlwind audition process later, Lyla find herself whisked off to a tropical paradise with Nico, boating through the Indian Ocean towards Ever After Island, where the two of them will compete against four other couples--Bayer and Angel, Dan and Santana, Joel and Romi, and Conor and Zana--in order to win a cash prize. But not long after they arrive on the deserted island, things start to go wrong. After the first challenge leaves everyone rattled and angry, an overnight storm takes matters from bad to worse. Cut off from the mainland by miles of ocean, deprived of their phones, and unable to contact the crew that brought them there, the group must band together for survival. As tensions run high and fresh water runs low, Lyla finds that this game show is all too real--and the stakes are life or death"--
113994
Keywords: Couples -- Fiction; Man-woman relationships -- Fiction; Islands -- Fiction; Actors -- Fiction; Survival -- Fiction; Reality television programs -- Fiction; Fiction -- Thrillers -- Suspense; Survival after airplane accidents, shipwrecks, etc; Islands -- Fiction; Suspense fiction; Thrillers (Fiction); Psychological fiction; Novels; Romans